2016
DOI: 10.1080/15389588.2016.1172703
|View full text |Cite
|
Sign up to set email alerts
|

The theory of planned behavior (TPB) and texting while driving behavior in college students

Abstract: Objective To examine the role of intent and other Theory of Planned Behavior (TPB) constructs in predicting college students’ willingness to texting while driving (TWD). Methods This was an, cross-sectional study. Two hundred and forty-three male and female college students enrolled in the 2013–2014 academic year in the College of Health, Human Services & Nursing completed a survey on TWD. Inclusion criteria: All races and ethnicities, ≥ 18 years of age, own a cell phone, and drive a car. Results Over 70% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 41 publications
13
44
0
Order By: Relevance
“…found that drivers of lower perceived behavioral control had less intention of unsafe-driving behaviors (e.g., text reading while driving). [ 36 ] The above-mentioned research findings approved the present results concerning drivers' perceived behavioral control. In a number of cases, high perceived behavioral control leads to an intention and performance of unsafe behavior.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…found that drivers of lower perceived behavioral control had less intention of unsafe-driving behaviors (e.g., text reading while driving). [ 36 ] The above-mentioned research findings approved the present results concerning drivers' perceived behavioral control. In a number of cases, high perceived behavioral control leads to an intention and performance of unsafe behavior.…”
Section: Discussionsupporting
confidence: 88%
“…'s research, drivers who were used to reading and writing text messages while driving tended to do so in the future much more than others. [ 36 ] In some other research by Ketphat et al ., the habit of watching sports matches showed to affect the driving speed. [ 23 ] Past behaviors showed to be a strong predictor in comparison to other factors in O'Callaghan and Nausbaum's investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Speeding and drinking & driving are widely prevalent and the causes of a large number of fatal crashes in virtually all countries (WHO, 2015), particularly among young drivers who seek sensation (Cestac, Paran, & Delhomme, 2011;Simons-Morton et al, 2012) and have difficulties in identifying road hazards because of their lack of driving experience (Scott-Parker, Hyde, Watson, & King, 2013). Additionally, related to the rapid growth in use of mobile phones (Vorderer, Krömer, & Schneider, 2016), the use of phones while driving has become a serious threat to road safety (WHO, 2015) as it causes cognitive, manual, visual, and auditory distraction (Caird, Johnston, Willness, Asbridge, & Steel, 2014 (Cestac et al, 2011;Møller & Haustein, 2014;Simons-Morton et al, 2012), drinking & driving (Åberg, 1993;Beck, 1981;Kenney et al, 2013;Zhang, Wieczorek, & Welte, 2012), as well as texting & driving (Bazargan-Hejazi et al, 2017;Gauld, Lewis, & White, 2014;Nemme & White, 2010). However, informed by the TPB (Ajzen, 1991), previous studies have mostly focused on individuals' normative perceptions and did not consider actual collective norms 1 .…”
Section: The Case Of Examinationmentioning
confidence: 99%
“…These normative perceptions are influential because the drivers identify with their peer groups and align their own behaviors in order not to be aberrant (this is the injunctive norms-based motivation of affiliation) and "to do the right thing" (Rimal & Lapinski, 2015, p. 397; motivation for complying with descriptive norms, see also Cialdini et al, 1990). Given the state of research on the influence of perceived norms on a wide range of risk behaviors (see Berkowitz (2004) for a review)among others, speeding, drinking & driving, and texting & driving (e.g., Åberg, 1993;Bazargan-Hejazi et al, 2017;Cestac et al, 2011)-, we hypothesize that perceived descriptive and injunctive norms are positively correlated with risk behavior. At the collective level, descriptive norms refer to the actual road traffic risk behavior enacted by peers and injunctive norms pertain to the peers' actual attitudes towards the risk behavior in question.…”
Section: H1: Risk Behaviors Vary Across Peer Groupsmentioning
confidence: 99%
“…Further, the development of cell phone interventions may be useful for individuals caught repeatedly violating laws prohibiting texting and driving. The theory of planned behavior has previously been employed to better understand cell phone use [43][44][45][46]. However, these have been cross-sectional [43][44][45] or have not yet reported the randomized findings [46].…”
Section: Discussionmentioning
confidence: 99%